Disponibilidade de n e k no solo e sua absorção pela videira de vinho fertirrigada no semiárido - Silva, Alexsandro Oliveira da [UNESP] (2015)
Viticulture is one of the main economic activity in the Lower-Middle São Francisco Valley, where wines and juices have been produced. Therefore, an experiment was carried out at Embrapa Tropical Semi-Arid, in Petrolina, State of Pernambuco, Brazil, to obtain information on the use of nitrogen and potassium fertigation in wine vines. The grapevine (Vitis vinifera L.) cv. Syrah is one of the main varieties cropped in the region. It was grafted onto the rootstock 1103 Paulsen, and plaanted in April 30, 2009, in a grid spacing of 1 m between plants and 3 m between rows in an Acrisol (Argissolo Vermelho Amarelo as in the Brazilian Soil Classification System). The trellis system used was cordon with three wires and the irrigation system was the drip with emitters of 4.5 L h-1 flow rate spaced at 0.5 m. Three growing seasons were evaluated: from June 17 to October 8, 2013, to February 7 to June 9, 2014, and August 6 to November 25, 2014. The treatments were five doses of nitrogen (0, 15, 30, 60 and 120 kg ha-1) and five doses of potassium (0, 15, 30, 60 and 120 kg ha-1) applied by the drip irrigation system. The concentration of NO3- and K+ in the soil solution was monitored by porous cup extractors. Plant nutritional status was monitored by petiole sap and leaf analysis. The assessment of plant productivity was performed using the total cluster weight per plant, average weight of cluster, and number of cluster per plant. Phenolic compounds, organic acids and nutrient analysis were performed on grapes in each growing season. Data were subjected to analysis of variance (F test) at 1% (0.01 >p) and 5% (0.05>p) and then the regression analysis was performed. The fertilizer levels did not influence the concentration of nutrients in the soil. Soil pH was influenced by nitrogen fertilization, increasing its acidity with increasing levels of N. The porous ...